2005
DOI: 10.1007/s00013-004-1124-x
|View full text |Cite
|
Sign up to set email alerts
|

Groups with isomorphic Burnside rings

Abstract: We prove that for some families of finite groups, the isomorphism class of the group is completely determined by its Burnside ring. Namely, we prove the following: if two finite simple groups have isomorphic Burnside rings, then the groups are isomorphic; if G is either Hamiltonian or abelian or a minimal simple group, and G is any finite group such that B(G) ∼ = B(G ), then G ∼ = G .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…If one imposes further restrictions on the groups, then the answer can become affirmative, an instance of this occurring in [13] where it is shown that the answer to Yoshida's question is positive in the case when both groups are abelian or Hamiltonian, and in [11] in the case when just one of them is hamiltonian or abelian or in the case when both groups are simple.…”
Section: Introductionmentioning
confidence: 91%
“…If one imposes further restrictions on the groups, then the answer can become affirmative, an instance of this occurring in [13] where it is shown that the answer to Yoshida's question is positive in the case when both groups are abelian or Hamiltonian, and in [11] in the case when just one of them is hamiltonian or abelian or in the case when both groups are simple.…”
Section: Introductionmentioning
confidence: 91%
“…Since the Burnside ring B(G) can be embedded in D(G), there is a connection to the similar problem concerning the ring B(G). This problem has been studied in [6,14,16], among others. Considering results for the isomorphism problem for Burnside rings it seems to be useful to work with primitive idempotents of In the second section we give a survey over the construction of D(G), the species and the primitive idempotents of Q(ζ ) ⊗ Z D(G) (ζ ∈ C primitive |G|-th root of unity).…”
Section: Introductionmentioning
confidence: 98%